SOCIAL ENTREPRENEURSHIP AS THE SAVIOR OF FOOD SECURITY ISSUES AMONG THE ELDERLY: A PROPOSAL - Ramlee, Shamshubaridah (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Food security among senior citizen is a new phenomenon inthe caring of senior citizens. Apart from making foodaffordable with the required nutrients, sustainability of thesupply at affordable prices is of utmost importance. Relyingon government funds as in most care centers in Malaysia;and donations in providing food to enhance the better healthqualities is not sustainable. In a Laureate project involving aliving lab in the outskirts of Kuala Lumpur, we piloted acaring service to transform the well-being of the seniorcitizens. With the community assets available in the vicinityof the lab, we present a proposal on monetizing thecommunity assets available around the senior citizenâshome. Solving the food security problem will beapproached from the perspective of social entrepreneurshipwhere an initial proposal of a community based foodsecurity project is proposed, known as the Enterprise SocialPreneur Project. This paper will introduce the trends of theaging society in Malaysia and define food security in thecontext of social entrepreneurship. This will be followed bya description of the Laureate project at the Al-Fikrah LivingLab where the idea of food security started. The nextsection will discussed on the findings of the communityassets and finally propose a solution to ensure sustainabilityof the food security and caring services from among thesenior citizens.KEY WORDS: Social business, enterprise social preneur, Food Safety,Health Qualities, Senior Citizen, Al-Fikrah Living Lab.